Exploring the role of Bisphenol A in obesity-driven colorectal cancer progression: network toxicology and multi-organ pathology in animal models - Saad, Muhamad Fikri Shazlan; Abdullah, Muhammad Nazrul Hakim; Lim, Vuanghao; Bahari, Hasnah; Khoo, Boon Yin; Tan, Jun Jie; Yong, Yoke Keong (Academic Press, 2025)
Bisphenol A (BPA), an endocrine disruptor, is linked to cancer progression in estrogen-responsive tissues, but its role in promoting colorectal cancer (CRC) progression in the context of obesity remains underexplored. This study examines BPA's influence on CRC in obese Sprague-Dawley rats using network toxicology and experimental models. Computational analysis using the Database for Annotation, Visualization, and Integrated Discovery identified pathways such as “CRC” and “chemical carcinogenesis-receptor activation”, implicating the PI3K-AKT pathway in IL-1 beta upregulation and BPA's role in CRC during obesity. Thirty male rats were grouped (n = 6) as follows: N (normal diet), NC (normal diet + CRC), HC (high-fat diet + CRC), NCB (normal diet + CRC + BPA), and HCB (high-fat diet + CRC + BPA). CRC was induced with 1,2-dimethylhydrazine (40 mg/kg), and BPA (25 mg/kg) was administered for 19 weeks. Although BPA exposure did not affect body weight or biochemical parameters, the HCB group exhibited significant histopathological changes in the colon, including lymphoid hyperplasia, liver damage, and increased IL-1β levels. Furthermore, diet influenced adipocyte size, exacerbating BPA's effects on CRC progression. Findings suggest BPA may worsen CRC progression in obese rats through identified pathways, promoting multi-organ pathology and underscoring the need for stricter regulations, especially for vulnerable populations.